Late-onset rheumatoid arthritis has a similar time to remission as younger-onset rheumatoid arthritis: results from the Ontario Best Practices Research Initiative - Li, Xiuying; Cesta, Angela; Movahedi, Mohammad; Bombardier, Claire (Arthritis research & therapy, 2022)
Background The prevalence of rheumatoid arthritis (RA) in persons 60 years or older is estimated to be 2%. Late-onset rheumatoid arthritis (LORA) is traditionally defined as the onset of RA after the age of 60 years. Compared to younger-onset rheumatoid arthritis (YORA) which occurs before the age of 60 years, LORA has unique characteristics and disease manifestations. To date, few reports have addressed LORA and the prognosis of LORA patients remains unclear. We compared the clinical characteristics, time to remission and treatment regimen at remission between LORA and YORA patients. Methods This prospective cohort study used a registry database in Ontario, Canada from 2008 to 2020. Patients were included if they had active rheumatoid arthritis (RA) disease (≥1 swollen joint) and were enrolled within 1 year of diagnosis. LORA was defined as a diagnosis of RA in persons 60 years and older and YORA as a diagnosis of RA in persons under the age of 60. Remission was defined by Disease Activity Score 28 (DAS28) ≤2.6. A multivariable Cox proportional hazards model was used to estimate time to remission. Results The study included 354 LORA patients and 518 YORA patients. The mean (standard deviation) baseline DAS28 score was 5.0 (1.3) and 4.8 (1.2) in LORA and YORA patients, respectively ( p =0.0946). Compared to YORA patients, the hazard ratio for remission in LORA patients was 1.10 (95% confidence interval 0.90 to 1.34 p =0.36) after adjusting for other prognostic factors. For patients who reached remission, LORA patients were less likely to be on a biologic or Janus kinase (JAK) inhibitor (16% vs. 27%) and more likely to be on a single conventional synthetic disease-modifying anti-rheumatic drugs (csDMARD) (34% vs. 27%) than YORA patients ( p =0.0039). Conclusion LORA and YORA patients had similar prognosis in terms of time to remission. At remission, LORA patients were more likely to be on a single csDMARD without a biologic or JAK inhibitor.